(untitled) (Eurasian Journal of Ecology, 2016)
Reasons for the deterioration of the epidemiological situation in the pig farms are often poorly understood skid previously unknown infection. The results of comparative tests of two ELISA test systems designed for the serological diagnosis of reproductive and respiratory syndrome virus.